2017
DOI: 10.18203/2349-2902.isj20171613
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of major limb amputations: a cross sectional study from a South Indian tertiary care hospital

Abstract: Background: Limb loss to amputation is a major problem especially in developing countries where majority of the cases are preventable. It is a burden, not just for the patient, but also for their care givers which imposes tremendous financial and psychological burden upon them. The aim was to outline the patterns, indications and short term complications of major limb among patients attending Government Medical College, Kozhikode, Kerala, India which is a tertiary care centre.Methods: This was a prospective, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
4
2
0
Order By: Relevance
“…The ipsilateral revision rate of BKA to AKA in our study 10.0%) was in accordance with revision rates reported by Aulivola et al and Dillingham et al [7, 12] However, our revision rates were lower than those reported by Cruz et al (12%) and Lim et al (17.6%) [10, 15], and higher than those reported by Unnikrishnan et al [18] The immense disparity in the revision rates reported in the literature may be due to poor primary assessment of the amputation level by training residents, poor management of the amputation stump, and the high risk of falls for this frail patient cohort, all of which may lead to stump dehiscence. Our favourable revision rates might be explained by the increased number of surgeries performed by vascular surgeons over the past 6 years, with 90.0% of MLEA procedures performed by vascular surgeons in 2017 compared to 21.4% in 2012.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ipsilateral revision rate of BKA to AKA in our study 10.0%) was in accordance with revision rates reported by Aulivola et al and Dillingham et al [7, 12] However, our revision rates were lower than those reported by Cruz et al (12%) and Lim et al (17.6%) [10, 15], and higher than those reported by Unnikrishnan et al [18] The immense disparity in the revision rates reported in the literature may be due to poor primary assessment of the amputation level by training residents, poor management of the amputation stump, and the high risk of falls for this frail patient cohort, all of which may lead to stump dehiscence. Our favourable revision rates might be explained by the increased number of surgeries performed by vascular surgeons over the past 6 years, with 90.0% of MLEA procedures performed by vascular surgeons in 2017 compared to 21.4% in 2012.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, there is a wide variation in the reported indications for MLEA. Unlike developed countries, where peripheral arterial disease remains the most common indication for MLEA [1417], in our series, DFS was the leading indication for MLEA, and this was consistent with other reports from developing nations [1822]. This is not surprising given that diabetes leads to peripheral arterial disease and three-quarters of MLEA procedures are performed for diabetic patients [11].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…21 The emergence of non-communicable diseases (NCDs) such as peripheral vascular disease, diabetes and leg gangrene as causes for major limb loss is in keeping with the increasing importance of NCDs in the overall disease burden in Sub Saharan Africa. The mortality rate after major amputation was 9.9% in our study and compares with the findings of Unnikrishnan et al 22 The incidence of stump infection after amputation surgery in Africa has been reported to be between 13 -77% depending on the choice of peri-operative prophylactic antibiotic use. 23 We did not have data on the antibiotics used in our patients, but the infection rate in our cohort (12.8%) compares very well with data from South Africa in patients in whom amoxicillin and clavulanic acid was used in combination for prophylaxis.…”
Section: Discussionsupporting
confidence: 86%
“…3 In a service dedicated for diabetic foot and vascular diseases, 81 planned amputations were performed in one and a half year in a center in Kozhikode. 4 After studying the causes of amputation in young men from Illinois, USA, Lambert and Sciora 5 found that trauma was the most common, accounting for 52% of all amputations. Later, Warren and Kihn 6 reported that 76% of 1,964 amputees who received treatment at the Veterans Administration Hospital had undergone amputation because of vascular insufficiency.…”
Section: Discussionmentioning
confidence: 99%